Safety and feasibility of laparoscopic surgery for elderly rectal cancer patients in Japan: a nationwide study. Issue 2 (11th April 2021) - Seishima, R; Miyata, H; Okabayashi, K; Hasegawa, H; Tsuruta, M; Shigeta, K; Monno, M; Yamashita, Y; Inomata, M; Wakabayashi, G; Kakeji, Y; Kitagawa, Y; et al.
Abstract: Background: This study aimed to analyse the perioperative results from a national dataset of rectal cancer resections in elderly patients. Methods: The clinical records of patients undergoing rectal cancer surgery between 2012 and 2014 were retrieved from the Japanese National Clinical Database and analysed retrospectively. Patients were categorized according to age and those 80 years or older were defined as elderly. Subgroups were also defined according to the surgical approach (laparoscopy versus open surgery). The short-term outcomes, including mortality, anastomotic leak, surgical site infections and medical complications were compared between subgroups. Results: Of 56   175 patients undergoing rectal cancer surgery, some 6717 patients were elderly and laparoscopy was performed in 46.8 per cent of the sample. When comparing laparoscopy and open surgery in elderly patients, the operative mortality rate (1.5 versus 2.8 per cent; P  <   0.001), the incidence of anastomotic leakage (5.2 versus 6.5 per cent; P  =   0.026), surgical site infections (6.0 versus 8.0 per cent; P  =   0.001), pneumonia (1.4 versus 2.5 per cent; P  =   0.001), renal failure (0.7 versus 1.3 per cent; P  =   0.016) and cardiac events (0.3 versus 0.8 per cent; P  =   0.008) were lower for laparoscopy than for open surgery. The overall complication rate in elderly patients (19.5 per cent) was comparable to that in the younger group ( P  =   0.07). However, incidence of systemic complications was significantly higher in elderly than in younger patients (all P  <   0.001). Conclusion: Laparoscopy was safe and feasible in elderly patients compared with open surgery. However, the rates of systemic complications were significantly higher than in younger patients. Abstract : A nationwide retrospective cohort study was conducted to assess the safety and feasibility of laparoscopic surgery (LAP) for elderly patients with rectal cancer. LAP is safe and feasible in elderly patients; however, the rate of some systemic complications is significantly higher than those in young patients.